Physical literacy-based intervention for older adults: a cluster randomized controlled trial study protocol - Sum, Raymond Kim Wai; Yang, Yijian; Choi, Siu Ming; Duncan, Michael J.; Li, Minghui (Frontiers in Sports and Active Living, 2024)
The ageing population creates concerns and challenges worldwide. The large number of older adults (aged over 65) in Hong Kong continues to rise as people live longer. This may result in heavy burdens on public services and problems such as a shortage of medical resources. The purpose of this study is to implement a physical literacy-based intervention among older adults in Hong Kong in order to achieve the goal of health promotion. A two-arm cluster randomized controlled trial will be employed in this proposed study. Ten daycare centers for the older adults in Hong Kong will be invited to participate in this study. The intervention group will receive functional fitness training and mastering physical literacy class twice a week with buddy peer support, and they will be asked to keep a reflective writing journal on a daily basis for 12 weeks in total. Participants will be evaluated at baseline (week 0), post-intervention (week 12), and at 6-week follow-up (week 18). This will consist of objective and self-reported measures covering elements within physical literacy (i.e., physical competence, motivation and confidence, knowledge and understanding) and also physical activity levels on an individual basis. The study intends to introduce a conceptual framework of physical literacy for the older adults through an intervention that allows older people to develop daily behaviour habits, which should promote active ageing for the older adults and greater self-esteem in later life. After this study, participants may share their positive experiences, and encourage their peers in the community to become physically literate in the future. In the long run, due to the feasibility and sustainability of these potential programs, this proposed study has the potential to connect seniors through social engagement and contribute to healthy living. Clinical trial approval from the National Library of Medicine (Reference number: NCT06137859).